Corrosion inhibition of carbon steel in HCl solution by some plant extracts - Singh, A.; Ebenso, E.E.; Quraishi, M.A. (My University, 2012)
The strict environmental legislations and increasing ecological awareness among scientists have led to the development of "green" alternatives to mitigate corrosion. In the present work, literature on green corrosion inhibitors has been reviewed, and the salient features of our work on green corrosion inhibitors have been highlighted. Among the studied leaves, extract Andrographis paniculata showed better inhibition performance (98%) than the other leaves extract. Strychnos nuxvomica showed better inhibition (98%) than the other seed extracts. Moringa oleifera is reflected as a good corrosion inhibitor of mild steel in 1 M HCl with 98% inhibition efficiency among the studied fruits extract. Bacopa monnieri showed its maximum inhibition performance to be 95% at 600 ppm among the investigated stem extracts. All the reported plant extracts were found to inhibit the corrosion of mild steel in acid media.
Keywords: Carbon steel; Corrosion inhibitors; Plant extracts; Andrographis paniculata; Corrosion inhibition; Ecological awareness